Pharmacological inhibition of Septins with Forchlorfenuron attenuates thrombus formation in experimental thrombotic mice models with modulating multiple signaling pathways in platelets - Zhen Hao; Minghui Yan; Reyisha Tuerhong; Luying Zhang; Zhen Zhang; Habib Alam; Jun Wu; Yuanhua Qin; Feng Zhao; Lei Shi (Journal of Advanced Research)
Introduction: The Septin family of cytoskeletal proteins is abundant in platelets. When these proteins are functionally blocked using the compound forchlorfenuron (FCF), it hampers the normal activation processes of purified human platelets. Objectives: To evaluate the in vivo effects of FCF on physiological haemostasis and pathological thrombosis in mice and to investigate possible molecular mechanisms. Methods: The impact of FCF on haemorrhage risk in the brain, liver, and tail of mice was investigated. Using several experimental models, thrombus development in the lung, mesenteric arteries, and postcava was studied. Functional assays were performed on mice and human platelets, both with and without FCF pretreatment. These tests included aggregation, granule release, ROS production, integrin αIIbβ3 activation, cytoskeletal remodeling imaging, and clot retraction. Results: Neither oral nor intravenous administration of FCF showed any apparent impairment of haemostasis in the tissues studied, but only later administration resulted in a significant reduction in thrombus formation in different mice vessel types. FCF generally inhibited agonist-induced platelet aggregation, degranulation, ROS burst, morphological expansion on the fibrinogen matrix with completely disordered dynamic organizations of the cytoskeleton for septin, tubulin and actin. In addition, FCF was found to antagonise agonist-induced dephosphorylation of VASP (Ser239) and PI3K/AKT and ERK1/2 phosphorylation. Conclusion: FCF showed preferences in attenuating pathological thrombus formation, apart from physiological haemostasis, with possible mechanisms to prevent cytoskeletal remodelling and signal transduction of AKT, ERK1/2 and VASP signalling pathways, suggesting that Septin may serve as a promising target for the prevention and treatment of thrombotic diseases.